(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Regarding a research project voted to the study of the so-called rock sanctuaries, this work aims to discuss the major problems within and in which way can its typological study be useful. Based on some specific examples, it will explore the special features that this kind of structures may present, which criteria should be considered to classify a place as a rock sanctuary and which typological groups can be distinguished according to this methodology.